Pengaruh Finansial Technology Literasi Keuangan terhadap Kinerja UMKM dengan Inklusi Keuangan sebagai Variabel Moderasi : Studi Kasus Usaha Mikro di Kota Bandar Lampung - Sopiyan Adi Permana; Irawan Irawan; Endang Asliana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
With financial inclusion acting as a moderator, the goal of this study is to examine how financial technology use and financial literacy impact microbusiness performance. Microbusinesses in Bandar Lampung City's food and beverage industry serve as the research subjects. This study employs a quantitative approach, using questionnaires to collect primary data from microenterprises. Purposeful sampling was used to choose 203 microbusinesses that met the research criteria. SPSS was utilized to analyze the data using multiple linear regression and Moderated Regression Analysis (MRA). The study's conclusions imply that the use of financial technology has an effect on microenterprises' performance. Additionally, it has been shown that financial literacy affects microenterprise performance. The findings show that key components in increasing microbusiness performance are the use of financial technology and the entrepreneur's capacity to supervise and make financial decisions. However, the test results indicate that financial inclusion cannot boost the impact of financial technology and financial expertise on microbusiness performance. This implies that the influence of financial technology and financial knowledge on business success is not necessarily enhanced by having access to financial services. It also shows that a key factor in increasing the success of microbusinesses is the characteristics of the entrepreneur. The research's objectives are to assist important stakeholders in creating plans for microenterprise growth, as well as to assist microenterprise actors in improving their financial literacy and utilizing financial technology to its fullest.